Effect of nickel on microstructure and mechanical properties of heat affected zone of low carbon steel - Eroglu, M; Aksoy, M (Maney Publishing, 2002)
In the present study, the effect of nickel along with varying heat input on the microstructure and mechanical properties of the heat affected zone (HAZ) of a low carbon steel was investigated. Experiments were carried out in which low carbon steel specimens with five different nickel contents, 1, 2, 2.9, 4.1, and 5.2 wt-%, were welded using a submerged are welding machine with heat inputs of 0.5, 1, and 2 U mm(-1). Following welding, the microstructure, hardness, and toughness of the HAZs were determined. From the results, attempts were made to establish a relationship between heat input, nickel content, microstructure, hardness, and toughness. Charpy impact testing and microstructural observation showed that, for a heat input of 0.5 U mm(-1), nickel contents between 2.9 and 5.2 wt-% were effective in forming lower transformation products, such as martensite, thereby producing lower toughness values. It was subsequently found that, taking into consideration the microstructure, hardness, and toughness of the HAZ, a lower heat input for a nickel content of I wt-% and a medium heat input for nickel contents between 2 and 5.2 wt-% gave good results.
Keywords: Initial Grain-Size; Weld Metal; Toughness; Strength; Haz; Mn